2021
DOI: 10.1016/j.prdoa.2021.100096
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacologic interventions to treat apathy in Parkinson’s disease: A realist review

Abstract: Highlights Nine studies explore non-pharmacological treatment of apathy in Parkinson’s disease. Exercise targets goal-directed behaviour change and engagement in social interactions. Mindfulness targets emotional, cognitive, and goal-directed domains of apathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In patients whose striatal DAT SBR is particularly low, there is a scope to monitor apathy and anhedonia symptoms, or to intervene early with interventions such as behavioural activation therapy which has been shown to be potentially effective in treating these symptoms in PD. 43 However, further validation of striatal DAT SBR as a potential marker of apathy/anhedonia risk is needed, especially as the Robin-Hood algorithm used in the two-lines test primarily tests for the presence of a threshold effect and cannot precisely identify the true turning point value.…”
Section: Discussionmentioning
confidence: 99%
“…In patients whose striatal DAT SBR is particularly low, there is a scope to monitor apathy and anhedonia symptoms, or to intervene early with interventions such as behavioural activation therapy which has been shown to be potentially effective in treating these symptoms in PD. 43 However, further validation of striatal DAT SBR as a potential marker of apathy/anhedonia risk is needed, especially as the Robin-Hood algorithm used in the two-lines test primarily tests for the presence of a threshold effect and cannot precisely identify the true turning point value.…”
Section: Discussionmentioning
confidence: 99%
“…In patients whose striatal DAT SBR is particularly low, there is scope to monitor apathy and anhedonia symptoms, or to intervene early with interventions such as behavioural activation therapy which has been shown to be potentially effective in treating these symptoms in PD. 38 However, further validation of striatal DAT SBR as a potential marker of apathy/anhedonia risk is needed, especially as the Robin-Hood algorithm used in the two-lines test primarily tests for the presence of a threshold effect and cannot precisely identify the true turning point value.…”
Section: Discussionmentioning
confidence: 99%
“…We assume that mindfulness has been a stabilizing factor preventing an increase of apathy in the training group. Previously, Mele et al (2021) concluded that mindfulness might indeed be useful to treat symptoms of apathy in PD especially in patients with higher motor impairment and mostly intact cognitive functioning.…”
Section: Discussionmentioning
confidence: 99%